Specification for polythene pipe ( type 32 ) for cold water services (BSI, 1967)
Polyethylene, Polymers, Plastics, Pipes, Water, Pressure pipes, Composition, Carbon black, Fillers, Antioxidants, Diameter, Thickness, Test pressure, Tensile strength, Materials in contact with food, Dimensions, Elongation at fracture, Potable water, Sampling methods, Marking, Coils, Length, Dimensional tolerances, Determination of content, Test specimens, Thermal testing, Hydraulic tests